Â€ACESSOJÂ€ AN APP TO EVALUATE THE ACESSIBILITY PLACES (CIPEEX, 2024)
THE DEVELOPMENT PROPOSAL FOR THE "ACESSOJ" APP AIMS TO ASSESS THE ACCESSIBILITY OF LOCATIONS COLLABORATIVELY, WHERE USERS THEMSELVES REPORT WHETHER A PARTICULAR ESTABLISHMENT, WHETHER PUBLIC OR PRIVATE, IS ACCESSIBLE. THIS INITIATIVE BENEFITS PEOPLE WITH DISABILITIES IN GENERAL, AS IT PROVIDES CRUCIAL INFORMATION FOR THEM TO PLAN THEIR ACTIVITIES MORE EASILY. A LOCATION-AWARE APP IS ESSENTIAL TO PROMOTE SOCIAL INCLUSION AND EQUALITY, ENSURING THAT ALL INDIVIDUALS, REGARDLESS OF THEIR PHYSICAL ABILITIES, CAN ENJOY THE SAME SPACES AND SERVICES. THIS NOT ONLY IMPROVES THE QUALITY OF LIFE FOR PEOPLE WITH DISABILITIES BUT ALSO STRENGTHENS THE VALUES OF EQUALITY AND DIVERSITY THROUGHOUT SOCIETY.THE "ACESSOJ" SOFTWARE PROJECT WILL ALSO HAVE A SIGNIFICANT IMPACT ACROSS VARIOUS AREAS AND GROUPS OF PEOPLE. ITS INFLUENCE EXTENDS THE ADVANCEMENT OF ACCESSIBILITY IN PUBLIC AND PRIVATE ESTABLISHMENTS, CONTRIBUTING TO THE PROMOTION OF SOCIAL INCLUSION FOR PEOPLE WITH DISABILITIES. MOREOVER, IT PLAYS A FUNDAMENTAL ROLE IN CULTURAL CHANGE TOWARDS ACCESSIBILITY AND INCLUSION, ENCOURAGING A MORE CONSCIOUS AND OPEN SOCIETY TO THE NEEDS OF ALL ITS MEMBERS.USER COLLABORATION IS CRUCIAL FOR THE ONGOING SUCCESS OF THE APP. BY SHARING THEIR ASSESSMENTS OF THE ACCESSIBILITY OF THE PLACES THEY VISIT, USERS ARE INSTRUMENTAL IN BUILDING A RELIABLE AND UP-TO-DATE DATABASE. THIS INFORMATION NOT ONLY HELPS PEOPLE WITH DISABILITIES MAKE INFORMED CHOICES BUT ALSO MOTIVATES ESTABLISHMENT OWNERS TO IMPROVE THEIR FACILITIES TO CATER TO A MORE DIVERSE AUDIENCE.IN SUMMARY, THE "ACESSOJ" SOFTWARE PROPOSAL IS NOT JUST A TECHNOLOGICAL TOOL BUT A VEHICLE FOR SOCIAL AND CULTURAL CHANGE. ITS MISSION TO PROMOTE ACCESSIBILITY AND INCLUSION IS A BENEFICIAL CONTRIBUTION TO BUILDING A FAIR AND EGALITARIAN SOCIETY, WHERE ALL INDIVIDUALS HAVE THE OPPORTUNITY TO VISIT ANY ESTABLISHMENT REGARDLESS OF THEIR PHYSICAL ABILITIES. THEREFORE, SUPPORTING AND SPREADING THE USE OF THIS APP IS ESSENTIAL TO ACHIEVING THIS GOAL.